2022
DOI: 10.1016/j.cegh.2021.100958
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of quality of sleep with cognitive performance and emotional maturity among adolescents

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The first is the evolutionary development itself; that is, the maturation (emotional) processes that occur at these ages. This conclusion coincides with other previous studies [67,68]. The second is at the end of compulsory secondary education when students define their own curricular development (preferably in the fourth year).…”
Section: Discussionsupporting
confidence: 91%
“…The first is the evolutionary development itself; that is, the maturation (emotional) processes that occur at these ages. This conclusion coincides with other previous studies [67,68]. The second is at the end of compulsory secondary education when students define their own curricular development (preferably in the fourth year).…”
Section: Discussionsupporting
confidence: 91%
“…The present study depicted normal mean cognitive performance scores in older adults. There was no significant difference in mental state in the two groups, which is consistent with research done by Casavi et al (2022), where no statistically significant effects were shown for cognitive performance with sleep quality [ 46 ]. Mahfouz et al (2020) also found no statistical difference in sleep quality according to the stress level, and DASS score [ 7 ], while Aseem et al (2021) highlighted a significant link between cognitive performance and sleep quality [ 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…Cumulative cognitive scores were considered as they provide better comprehension of overall cognitive abilities of students, as opposed to the individual domain scores, as observed in previous studies for adolescent subjects. 22,32 The questionnaire was administered to the participants in a controlled setting, ensuring standardized conditions for data collection for all participants.…”
Section: Data Collectionmentioning
confidence: 99%
“…While originally designed for diagnosis of mild and severe cognitive impairments in the aged population by Nasreddine and colleagues, 20 MoCA and its vernacular versions have been efficiently extended to young adult and adolescent student populations in several studies. [21][22][23][24] Use of MoCA has also been undertaken specifically in Indian students. 25 Using these questionnaire-based instruments, in this study, we investigated the emotional status and cognitive functioning in university students for the exploration of any potential associations.…”
Section: Introductionmentioning
confidence: 99%